Atg16L2, a novel isoform of mammalian Atg16L that is not essential for canonical autophagy despite forming an Atg12–5-16L2 complex - Koutaro Ishibashi; Naonobu Fujita; Eiko Kanno; Hiroko Omori; Tamotsu Yoshimori; Takashi Itoh; Mitsunori Fukuda (2011)
A large protein complex consisting of Atg5, Atg12 and Atg16L1 has recently been shown to be essential for the elongation of isolation membranes (also called phagophores) during mammalian autophagy. However, the precise function and regulation of the Atg12–5-16L1 complex has largely remained unknown. In this study we identified a novel isoform of mammalian Atg16L, termed Atg16L2, that consists of the same domain structures as Atg16L1. Biochemical analysis revealed that Atg16L2 interacts with Atg5 and self-oligomerizes to form an ~800-kDa complex, the same as Atg16L1 does. A subcellular distribution analysis indicated that, despite forming the Atg12–5-16L2 complex, Atg16L2 is not recruited to phagophores and is mostly present in the cytosol. The results also showed that Atg16L2 is unable to compensate for the function of Atg16L1 in autophagosome formation, and knockdown of endogenous Atg16L2 did not affect autophagosome formation, indicating that Atg16L2 does not possess the ability to mediate canonical autophagy. Moreover, a chimeric analysis between Atg16L1 and Atg16L2 revealed that their difference in function in regard to autophagy is entirely attributable to the difference between their middle regions that contain a coiled-coil domain. Based on the above findings, we propose that formation of the Atg12–5-16L complex is necessary but insufficient to mediate mammalian autophagy and that an additional function of the middle region (especially around amino acid residues 229–242) of Atg16L1 (e.g., interaction with an unidentified binding partner on phagophores) is required for autophagosome formation.